Dielectric, ferroelectric and piezoelectric properties of 0-3 barium titanate-Portland cement composites - Rianyoi R. (2014)
In this work, barium titanate (BT) and cement composites of 0-3 connectivity were produced with BT concentrations of 30%, 50% and 70% by volume using the mixing and pressing method. The dielectric constant (εr ) and the dielectric loss (tan δ) at room temperature and at various frequencies (0.1-20 kHz) of the ferroelectric BT-Portland cement composites with different BT concentrations were investigated. The results show that the dielectric constant of BT-PC composites was found to increase as BT concentration increases, and that the highest value for εr-of 436-was obtained for a BT concentration of 70%. In addition, the dielectric loss tangent decreased with increasing BT concentration. Moreover, several mathematical models were used; the experimental values of the dielectric constants are closest to those calculated from the cube model. The 0-3 cement-based piezoelectric composites show typical ferroelectric hysteresis loops at room temperature. The instantaneous remnant polarization (Pir ), at an applied external electrical field (E0) of 20 kV/cm (90 Hz) of 70% barium titanate composite, was found to have a value ̃3.42 μC/cm2. Furthermore, the piezoelectric coefficient (d33) was also found to increase as BT concentration increases, as expected. The highest value for d33 was 16 pC/N for 70% BT composite. © Springer-Verlag 2011.